Local and Systemic Administration of Mesenchymal Stem Cells in Regeneration of Mandibular Defects: An Experimental Study - Khojasteh, Arash; Dehghan, Mohammad Mehdi; Motamedian, Saeed Reza; Farzad-Mohajeri, Saeed; Nazeman, Pantea; Nokhbatolfoghahaie, Hanieh; Alikhasi, Marzieh (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Mesenchymal stem cells (MSCs) have been utilized as an aid in regeneration of bone defects however due to the poor homing ability via systemic injection, local administration, genetic manipulation has been used more. The present study aimed to compare the local and systemic application of MSCs in regeneration of bone defects. Materials and Methods: Sixty Wistar male rats were used in this study. Circular 5×5 mm bone defects were created in the angle of the mandible. Autogenous bone marrow mesenchymal stem cells (BMMSCs) were obtained and culture expanded. Green fluorescent positive (GFP+) transfection has been performed for the possible detection of the cells in the healed bone. The rats were randomly treated in four groups; 1. Beta tricalcium phosphate (β-TCP) scaffold seeded with MSC (β-TCP+MSC), 2. Intravenous MSC injection with β-TCP scaffold in the defect (MSC), 3. β-TCP without cell therapy (β-TCP) and 4. Control defects that left empty. The rats were euthanized after 8 weeks. New bone formation (BF) were investigated by hematoxylin and eosin staining. Results: Localized cell therapy (β-TCP+MSC group) showed the highest healing rate (BF= 54.05±2.39%) followed by MSC systemic injection (BF= 22.69±3.87%) (P≤0.05). Inflammatory cells infiltration was evident dominantly in systemic injection cell group. Immunohistchemical analysis showed existence of the MSCs around the defects. GFP+ cells were mainly detected in the defect in β-TCP+MSC group while few GFP+ cells were detected in the MSC systemic group. Conclusion: local application of the MSCs with synthetic scaffold showed better results than intravenous administration of MSCs in treatment of rat mandible bone defects.